Medical residents' attitude toward professionalism and assessment of their professional behaviors: a cross-sectional survey - Navid Mohammadi; Habib Rahban; Abbas Allami (Tabriz University of Medical Sciences, 2018)
Background: Professionalism training is a core component of medical education. This study's aim was to determine medical residents' attitudes toward professionalism and self-reported professional behaviors. Methods: In a cross-sectional survey at Qazvin University of Medical Sciences, 100 medical residents in their first through third years were invited to participate in a survey between April and June of 2015. Participants responded to a written questionnaire consisting of 7 demographic and 42 content items in 4 domains. Content items were rated on a 5-point Likert scale. Results with a mean of less than three were considered undesirable. A non-parametric Kruskal-Wallis test was used to compare distributions in the study groups. All statistical analyses were performed using SPSS version 22. Results: With a response rate of 87%, a mean age of 31.9 (SD: 3.0) was recorded. The mean Likert score for the perception of residents on the ethical importance of "colleague report" and "reporting error" was undesirable. The percentage of residents' self-reported unprofessional behaviors during their training was high. Moreover, 71% (95% CI: 61-80) of residents believed that ethics should be formally taught in the medical school curriculum. Over 97% (95% CI: 94-100) believed that learning medical ethics and professionalism requires more than a theoretical course. A longitudinal approach was the most agreed-upon format. Conclusion: Based on the findings of this research, despite a relatively acceptable rate of professional behaviors, residents perceive a need for a more comprehensive curricular attention to practical ethics and ethically important professional development during residency training.